2020
DOI: 10.21203/rs.3.rs-22835/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A child confirmed COVID-19 with only symptoms of conjunctivitis and eyelid dermatitis

Abstract: The outbreak of the 2019 novel coronavirus disease (COVID-19) infection in China had quickly spread worldwide. Recent reports showed that conjunctivitis symptoms were found in a small number of adult patients diagnosed with COVID-19. But rare children diagnosed with COVID-19 were reported to have eye symptoms. Our case showed a 2 years and 10 months old child confirmed COVID-19 had no symptoms other than conjunctivitis and eyelid dermatitis, suggesting that doctors shouldn’t forget to conduct COVID-19 screenin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 17 publications
0
31
2
3
Order By: Relevance
“…The research of Wu et al(22) indicates that conjunctivitis and eyelid dermatitis may indicate COVID-19, as confirmed by molecular testing, real-time polymerase chain reaction (RT-PCR) on SARS-CoV-2.Collona et al in Italy, it describes frost-like changes in four children aged 5-11 years with mild symptoms of COVID infection, which they explained by a vaso-occlusive phenomenon due to elevated d-dimers (23).Andina et al(24) reported identical changes in Madrid in 22 children aged 6-17 years with moderate symptoms of COVID-19 disease. These atypical manifestations of COVID-19 disease did not require treatment and had a good prognosis(23,24).…”
mentioning
confidence: 99%
“…The research of Wu et al(22) indicates that conjunctivitis and eyelid dermatitis may indicate COVID-19, as confirmed by molecular testing, real-time polymerase chain reaction (RT-PCR) on SARS-CoV-2.Collona et al in Italy, it describes frost-like changes in four children aged 5-11 years with mild symptoms of COVID infection, which they explained by a vaso-occlusive phenomenon due to elevated d-dimers (23).Andina et al(24) reported identical changes in Madrid in 22 children aged 6-17 years with moderate symptoms of COVID-19 disease. These atypical manifestations of COVID-19 disease did not require treatment and had a good prognosis(23,24).…”
mentioning
confidence: 99%
“…Laboratory results: Complete blood counts may be normal, 11,14‐16,19,22,26,29,32,39,40,44,48‐50,54,61,79,93,102,165,168 or show either decreased 14,16,19,25,26,29,31,39,40,44,49,55,61,70,93,100,108 or elevated white blood cell counts 11,14,20,22,26,44,47,50,54,60,61,93,99 . Lymphocyte counts may be increased, 15,19,24,26,29,44,60,78,79,82,84,93,96,103,169 or decreased 14,19,22,23,25‐28,31,34,39,44,49,55,70,79,82,84,88,99,100,103,113,116 . Increased C‐reactive protein (CRP), 15,19,22,25,26,28,29,31,40,41,44,47,49,50,56,73,74,77,83,84,88,93,101,103,104 procalcitonin (PCT) 15,22,26,31,44,49,50,56,73,77,84,88,93,99 and lactate dehydrogenase 14,15,22,25,47,81,83,84,93 have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining are case reports by Khavandi et al [15], Colavita et al [16], Navel et al [17], Chen et al [18], Cheema et al [19], and Wu et al [20]. These case reports are of patients of various ages, including a child.…”
Section: Summary Of Study Findingsmentioning
confidence: 99%
“…To this end, different research teams have performed reverse transcription polymerase chain reaction (RT-PCR) on ocular samples of tears and conjunctival secretions, and viral cultures. What has been reported is that COVID-19 can be accompanied by conjunctivitis with its attendant symptoms of conjunctival infection, epiphora, itch, discharge, etc., but this remains a relatively rare occurrence compared with the classic respiratory symptoms [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It is questionable whether the eye is truly a portal of transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation